1991
DOI: 10.2105/ajph.81.2.168
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk behavior reduction following intervention with key opinion leaders of population: an experimental analysis.

Abstract: BACKGROUND AND PURPOSE. Peer norms influence the adoption of behavior changes to reduce risk for HIV (human immunodeficiency virus) infection. By experimentally intervening at a community level to modify risk behavior norms, it may be possible to promote generalized reductions in HIV risk practices within a population. METHODS. We trained persons reliably identified as popular opinion leaders among gay men in a small city to serve as behavior change endorsers to their peers. The opinion leaders acquired social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
394
0
5

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 646 publications
(411 citation statements)
references
References 7 publications
12
394
0
5
Order By: Relevance
“…24 Kelly and colleagues trained key opinion leaders in gay bars to interact with patrons and provide safe sex education, and found that after the intervention, condom usage increased 16% and unprotected anal sex decreased (36.9% vs. 27.5%). 25 Despite the success of interventions in LGBT bars and nightclubs to reduce HIV/ AIDS, a focus on bars to promote tobacco cessation has been largely unexplored. 26 The findings of this study complement other studies that suggest LGBT specific smoking cessation interventions may be optimal to address tobacco use among this group.…”
Section: Discussionmentioning
confidence: 99%
“…24 Kelly and colleagues trained key opinion leaders in gay bars to interact with patrons and provide safe sex education, and found that after the intervention, condom usage increased 16% and unprotected anal sex decreased (36.9% vs. 27.5%). 25 Despite the success of interventions in LGBT bars and nightclubs to reduce HIV/ AIDS, a focus on bars to promote tobacco cessation has been largely unexplored. 26 The findings of this study complement other studies that suggest LGBT specific smoking cessation interventions may be optimal to address tobacco use among this group.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion theory posits that behavioral change is achieved when information and ideas, such as new risk-reducing methods in the case of HIV prevention, is disseminated by opinion leaders through their personal and social networks (Sivaram et al, 2004). Kelly and colleagues have shown that systematically identified, recruited, and trained POLs make a positive impact on sexual behavior change in populations of men attending gay bars in the United States (Kelly et al, 1991;Kelly et al, 1992;Kelly et al, 1997). In the POL model, ethnographic techniques are employed to systematically identify popular and socially influential members of the target population.…”
mentioning
confidence: 99%
“…28,29 The popular opinion leader approach uses ethnographic research to identify particularly well liked and influential individuals within the community to receive training in how to deliver effective behavioural change messages to friends during everyday conversations. 30 Lesbian families of choice, by contrast, play a more private role in which intimate, caring relationships are central; as such, intervention approaches based on the natural helper or lay health advisor model could be particularly effective in making use of participants' desire to support and protect fellow family members from negative sexual health outcomes. [31][32][33][34] Many interventions based on the natural helper approach actively seek to identify those individuals known by their communities for their caring natures who will share important health information spontaneously as part of their regular interactions within the community.…”
Section: Discussionmentioning
confidence: 99%